Surface confined self-assembly of polyampholytes generated from charge-shifting polymers1. Issue 74 (25th September 2015) - Garnier, T.; Dochter, A.; Chau, N. T. T.; Schaaf, P.; Jierry, L.; Boulmedais, F.
<x xml:space="preserve">Abstract</x> Polyampholyte-based films can be efficiently self-assembled onto a surface in a one-pot manner by using a charge-shifting polyelectrolyte transformed into a polyampholyte by an electrogenerated gradient of protons.